A Secure Data Transmission Scheme using Asymmetric Semi-Homomorphic Encryption Scheme - S. Nagavalli; G. Ramachandran (Institute of Advanced Engineering and Science, 2018)
The compressive detecting based information accumulation accomplishes with high exactness in information recuperation from less inspection which is available in sensor nodes. In this manner, the existing methods available in the literature diminish the information gathering cost and delays the existence cycle of WSNs. In this paper, a strong achievable security model for sensor network applications was initially proposed. At that point, a secure data collection conspire was displayed based on compressive detecting, which improves the information protection by the asymmetric semi-homomorphic encryption scheme, and decreases the calculation cost by inadequate compressive grid. In this case, particularly the asymmetric mechanism decreases the trouble of mystery key circulation and administration. The proposed homomorphic encryption permits the in-arrange accumulation in cipher domain, and in this manner improves the security and accomplishes the adjustment in system stack. Further, this paper focuses on estimating various network performances such as the calculation cost and correspondence cost, which remunerates the expanding cost caused by the homomorphic encryption. A real time validation on the proposed encryption scheme using AVISPA was additionally performed and the results are satisfactory.